Anti-Allergic Effects of Lonicera caerulea L. Extract and Cyanidin-3-Glucoside on Degranulation and FcεRI Signaling Pathway of RBL-2H3 Cells - Ye-Eun Choi; Jung-Mo Yang; Chae-Won Jeong; Sung-Hwan Park; Hee-Won Yoo; Hyun-Duck Jo; Ju-Hyun Cho (Applied Sciences)
(i) Background: The increasing prevalence of allergic diseases highlights the need for effective treatments. Lonicera caerulea fruit has been recognized for its anti-inflammatory, anti-cancer, and neuroprotective effects, but the mechanisms underlying its anti-allergic properties remain unclear. (ii) Objective: This study aims to evaluate the total phenolic, total flavonoid, and cyanidin-3-glucoside (C3G) contents of Lonicera caerulea extract (HR2302-30E) and to investigate its antioxidant and anti-allergic activities. (iii) Methods: Using an IgE-stimulated RBL-2H3 cell model, we assessed the effects of HR2302-30E and C3G on mast cell degranulation, β-hexosaminidase and histamine release. Western blot analysis was performed to evaluate the expression of high-affinity IgE receptor (FcεRI)β/γ and the phosphorylation of Src family kinases (Syk, Fyn). We also examined the phosphorylation of downstream factors phospholipase Cγ, protein kinase Cδ, and mitogen-activated protein kinase. (iv) Results: Total phenolic, flavonoid, and C3G contents of HR2302-30E were 18.73 mg GAE/g, 11.83 mg QE/g, and 7.02 mg/g, respectively. In IgE-activated mast cells, HR2302-30E and C3G inhibited β-hexosaminidase and histamine release. Western blot analysis revealed reduced expression of FcεRIβ/γ and decreased phosphorylation of key downstream signaling molecules. Conclusions: These findings suggest that HR2302-30E and C3G modulate FcεRI signaling, indicating their potential as natural anti-allergic agents.